FORMULATION, CHARACTERIZATION AND OPTIMIZATION OF PLGA-CHITOSAN-LOADED FATTY ACID SCAFFOLDS FOR THE TREATMENT OF DIABETIC WOUNDS - THUMBOORU, SHILPA N.; AHMED, SYED SUHAIB; HARI, BALAJI; MP, GOWRAV; REDDY, KARRI VVS NARAYANA (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of the current research to formulate Eicosapentanoic Acid/Decosahexanoic Acid (EPA/DHA)incorporated into Chitosan (CS)and Poly-Lactic-Glycolic Acid (PLGA), nanoparticles composite scaffolds to the accelerated diabetic wound healing. The main focus of this present research is to evaluate and develop the chitosan–PLGA biodegradable polymer scaffolds loaded with long-chain omega-3 Polyunsaturated Fatty Acids (PUFA’s) (EPA/DHA). Methods: Nano scaffolds were prepared by solvent evaporation method loaded with CS-PLGA, EPA and DHA to treat diabetic wounds at targeted site as pharmacotherapeutically. Upon investigation, the developed biodegradable crosslinked scaffold possesses matrix degradation, optimal porosity, prolonged drug release action than the non-cross linked scaffold. The prepared formulation containing CS-PLGA loaded with EPA/DHA were formulated as nanoscaffold for wound topical applications was carried out by using freeze drying process. Results: The prepared CS-PLGA nano scaffolds were optimized and evaluated for physicochemical properties, dynamic light scattering with a particle size of 248 nm and zeta of-24mVand Scanning Electron Microscopy (SEM) were found to be spherical. In addition, the optical properties of EPA/DHA and PLGA, along with CS, can be compared by examining their absorption and wavelength (nm) using UV-visible spectroscopy. The structural and functional groups of the prepared end products were characterized by Fourier-Transformed Infrared Spectroscopy (FT-IR) has shown good compatibility with excipients and nanoformulaton, in vitro drug release studies done by using dialysis bag membrane results find that first-order Higuchi model was followed showing 20% release in first 0.2 h. MTT(3-(4,5-dimethylthiazolyl)-2,5-diphenyltetrazolium bromide) assay was carried out and it showed that both crosslinked and non-crosslinked scaffolds(110 and 120%) improved cell growth when compared to control (100%). Conclusion: Finally, the results showed that the PLGA, CS nanoscaffolds containing 98% of PUFA’s (EPA/DHA) have increased in proinflammatory cytokines production at the particular wound site and thus accelerated healing activity, depending on the pre-clinical studies have trespassed, the therapeutic potential to penetrating at wound site. The optimized nanoformulation could be a better formulation for targeting and treatment of diabetic wounds at an optimal ratio.